Pitfalls of Distinguishing Skull Metastases from Paragangliomas: A Case Report of a “Pseudo-angioma” Bone Metastasis - Roblot, Victoire; Dunas, Annelise; Bernat, Anne Laure; Bisdorff, Annouk; Deflorenne, Elisa; Bousson, Valérie (Seminars in Musculoskeletal Radiology, 2025)
A 22-year-old woman with persistent headaches was diagnosed with a right parietal bone lytic lesion with a sunburst pattern, suspected to be either an intraosseous hemangioma or a Langerhans cell histiocytosis. Five years later, progressively increased skull bone destruction, identification of retroperitoneal and lumbar vertebra lesions, and a biopsy of the skull led to the diagnosis of a retroperitoneal paraganglioma with bone metastases. Genetic testing identified an SDHBmutation. This case underscores the diagnostic challenge of metastases of paraganglioma mimicking hemangiomas and thus delaying appropriate management.
Keywords: paraganglioma; angioma; SDHB